Rancang Bangun Customer Relationship Management dengan K-Means untuk Reward Customer Berbasis Web - Barimbing, Angela Odetio; Hidayat, Rahmat Rian (Jurnal Teknik Informatika dan Sistem Informasi, 2024)
The continuous growth of the industry drives PT Porta Griya Indah, an industrial company, to retain their customers. Currently, the company still employs manual methods such as telephone, WhatsApp, and email to manage customer relationships, making it difficult for the marketing team to foster good relations. To overcome this challenge, the company needs to implement Customer Relationship Management (CRM) strategies. To increase sales and customer loyalty, the appropriate choice is to provide rewards to customers. Therefore, the aim of this research is to develop a simple web-based Customer Relationship Management application with K-Means Clustering algorithm, used to determine rewards for customers accurately and quickly. Data will be grouped into two clusters, namely eligible for rewards and not eligible for rewards, based on criteria and assessment weights. The research results indicate that this system helps the marketing team in communicating with customers, facilitating the conveyance of customer issues and needs to the directors, and facilitating the selection of the best customers eligible for rewards to enhance loyalty. The implementation of this system enhances the efficiency of PT Porta Griya Indah in retaining customers and increasing customer satisfaction amidst the continuously growing industry.